Study of Prevalence of Toxoplasma Gondii among Heamodialysis Patients in Thi-Qar Province - Bassad A. Al-Aboody (Journal of Global Pharma Technology, 2018)
Toxoplasmosis is a widespread zoonotic disease caused by one of opportunistic parasite called Toxoplasma gondii .The current study was conducted in Thi-Qar province to investigate the parasite Toxoplasma gondii among heamodialysis patients using Enzyme Linked Immunosorbent Assay test and study some of the factors that may affect in the prevalence of infection, such as age, sex and a number of heamodialysis. 100 was collected samples of blood  from heamodialysis patients  from Hussein Teaching Hospital for the period from October 2015 to the end of  March 2016 and prepared a questionnaire form for each person to get their information, as well as the collection of 50 blood samples from healthy persons for the purpose of comparison between them with the current study. The results of the current study showed that the prevalence of toxoplasmosis in Thi--Qar province in renal dialysis patients and a comparison group of 28% and 24% respectively. Recorded results of Enzyme Linked Immunosorbent Assay ELISA test results for a positive antibody IgG in heamodialysis patients and a comparison, 25 % 22% respectively. As for the IgM antibody study did not record any positive result in heamodialysis patients group while in comparison group was 2%. The ratios antibodies IgG & IgM together in heamodialysis patients and comparison group 3%, 0.0% respectively. The highest infection rates for heamodialysis patients was in the age group (40-49 years) was 26.67% and the lowest rates of infection in the age group (>60years) 23.08 %  and reported significant differences P <0.05 to infection rates in males highest compared to females where it was 35.18% and 19.56% respectively. For factor number of heamodialysis show high infection rates in patients who have been exposed to more than>6times of heamodialysis 25.53% as for those who were exposed to 1-6 was ratios have 16.67%.Keywords: Toxoplasma gondii, Toxoplasmosis,   Heamodialysis patients, Prevalence, ELISA, risk factors.